Protective Effect of a Cocoa-Enriched Diet on Oxidative Stress Induced by Intensive Acute Exercise in Rats - Patricia Ruiz-Iglesias; Malén Massot-Cladera; Maria J. Rodríguez-Lagunas; Àngels Franch; Mariona Camps-Bossacoma; Francisco J. Pérez-Cano; Margarida Castell (MDPI AG, 2022)
Intensive acute exercise can induce oxidative stress, leading to muscle damage and immune function impairment. Cocoa diet could prevent this oxidative stress and its consequences on immunity. Our aim was to assess the effect of a cocoa-enriched diet on the reactive oxygen species (ROS) production by peritoneal macrophages, blood immunoglobulin (Ig) levels, leukocyte counts, and the physical performance of rats submitted to an intensive acute exercise, as well as to elucidate the involvement of cocoa fiber in such effects. For this purpose, Wistar rats were fed either a standard diet, i.e., a diet containing 10% cocoa (C10), or a diet containing 5% cocoa fiber (CF) for 25 days. Then, half of the rats of each diet ran on a treadmill until exhaustion, and 16 h later, the samples were obtained. Both C10 and CF diets significantly prevented the increase in ROS production. However, neither the cocoa diet or the cocoa fiber-enriched diet prevented the decrease in serum IgG induced by acute exercise. Therefore, although the cocoa-enriched diet was able to prevent the excessive oxidative stress induced by intensive exercise, this was not enough to avoid the immune function impairment due to exercise.